How to Build a Supercomputer: U.S. Research Infrastructure and the Documents That Mitigate the Uncertainties of Big Science. (October 2020) - Read, Sarah
In this article, I argue that technical reporting and documentation processes function to mitigate uncertainty and enable complex systems in the endeavor of big science. The argument draws on two years of field research investigating technical reporting and documentation processes at a federally funded supercomputing center dedicated to scientific research. A central question the study sought to answer was, "How does one build a new supercomputer?" One of the answers that emerged is that supercomputers are built by the genre assemblages of documents that mitigate financial, political, and technological uncertainties, and their attendant risks, that are inherent to technoscientific cutting-edge enterprises. Given their centrality, these genre assemblages function as essential infrastructure for the U.S. national laboratory system and for big science endeavors in general. In conclusion, this article argues that documentation that mitigates uncertainty serves an important infrastructural function for organizational life more generally.